Diplomatic asylum and the Alan García case - Hernández Campos, Augusto (2020)
Diplomatic or political asylum is a relevant institution within the universal system of protection of human rights and fundamental freedoms. Although it is basically regulated in Latin America, there is also some practice in the rest of the world, even if in principle it is not granted legal recognition. In this sense, diplomatic asylum is acontribution made by Latin America, within the framework of International American Law, to International Human Rights and to International Law in general. Although diplomatic asylum is granted on the grounds of political persecution, in the case of Alan Garcia, Uruguay has denied this asylum as there were no political crimes. The purpose of this article will be to introduce some basic concepts about diplomatic asylum and thecase of Alan Garcia, where it was denied asylum because it was an investigation for common crimes.